Ethical and legal issues in psychedelic harm reduction and integration therapy - Pilecki, Brian; Luoma, Jason B.; Bathje, Geoff J.; Rhea, Joseph; Narloch, Vilmarie Fraguada (Harm reduction journal, 2021)
Psychedelic-assisted therapy may represent an upcoming paradigm shift in the treatment of mental health problems as recent clinical trials have demonstrated strong evidence of their therapeutic benefits. While psychedelics are currently prohibited substances in most countries, the growing popularity of their therapeutic potential is leading many people to use psychedelics on their own rather than waiting for legal medical access. Therapists therefore have an ethical duty to meet this need by providing support for clients using psychedelics. However, incorporating psychedelics into traditional psychotherapy poses some risk given their prohibited status and many therapists are unsure of how they might practice in this area. This paper explicates such risks and describes ways in which therapists can mitigate them and strive to practice within legal and ethical boundaries. A harm reduction approach will be emphasized as a useful framework for conducting therapy around clients' use of psychedelics. It is argued that therapists can meet with clients before and after their own personal psychedelic experiences in order to help clients minimize risk and maximize benefit. Common clinical scenarios in this growing clinical area will also be discussed.